Living in a dangerous world: the shaping of behavioral profile by early environment and 5-HTT genotype - Heiming, Rebecca S.; Jansen, Friederike; Lewejohann, Lars; Kaiser, Sylvia; Schmitt, Angelika; Lesch, Klaus Peter; Sachser, Norbert (Frontiers in Behavioral Neuroscience, 2009)
Anxiety and anxiety disorders are influenced by both, environmental and genetic factors. One genetic factor under scrutiny for anxiety disorders is the genetically encoded variation of the serotonin transporter (5-HTT). The aim of this study was to elucidate the effects of a threatening environment during early phases of life on anxiety-like (ANX) and exploratory behavior (EXP) in adult mice, varying in serotonin transporter (5-HTT) genotype. For this purpose, pregnant and lactating 5-HTT +/- dams were repeatedly exposed to olfactory cues of unfamiliar adult males by introducing small amounts of soiled bedding to their home cage. These stimuli signal the danger of infanticide and simulate a threatening environment. Control females were treated with neutral bedding. The offspring (5-HTT +/+, +/-, -/-) were examined for their ANX and EXP. The main results were: (1) a main effect of genotype existed, with 5-HTT -/- showing higher levels of ANX and lower levels of EXP than 5-HTT +/- and wildtypes. (2) When mothers had lived in a threatening environment, their offspring showed increased ANX and reduced EXP compared to controls. (3) These effects were most pronounced in 5-HTT -/- mice. By applying a new ecologically relevant paradigm we conclude: If 5-HTT +/- mothers live in a threatening environment during pregnancy and lactation, their offspring behavioral profile will, in principle, be shaped in an adaptive way preparing the young for an adverse environment. This process is, however, modulated by 5-HTT genotype, bearing the risk that individuals with impaired serotonergic neurotransmission (5-HTT -/-) will develop an exaggerated, potentially pathological level of anxiety from gene x environment interactions.